1986
DOI: 10.1099/00222615-22-4-325
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Vibrio cholerae mucinase complex. I. Enzymic activities associated with the complex325

Abstract: Summary. Mucinase enzymes were isolated and partially purified from the culture fluid of Vibrio cholerae grown in proteose peptone-colostrum medium. The mucinase complex contained neuraminidase, endo-P-N-acetylhexosaminidase, nicotinamideadenine-dinucleotidase and proteinases. Traces of phospholipase activity were detected but the complex lacked aldolase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…wt aggregate (c. 325 kDa), which possessed sialidase activity, was isolated as determined by native PAGE and gel filtration chromatography. It was not possible to purify cholerae has demonstrated that this enzyme forms a multi-enzyme complex, which contains other glycosidic and proteolytic activities [36]. Sialidase complexed with other enzymes, including â-galactosidase, is also found in human lysosomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…wt aggregate (c. 325 kDa), which possessed sialidase activity, was isolated as determined by native PAGE and gel filtration chromatography. It was not possible to purify cholerae has demonstrated that this enzyme forms a multi-enzyme complex, which contains other glycosidic and proteolytic activities [36]. Sialidase complexed with other enzymes, including â-galactosidase, is also found in human lysosomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical streptococcal isolates often secrete NADases (24), and an NADase activity distinct from cholera toxin has been described as an extracellular product of V. cholerae (52). Also, an ORF resembling HvnA and HvnB occurs in the P. aeruginosa genome, suggesting that this organism may also secrete an NADase.…”
Section: Fig 6 Product Analysis Of Nadmentioning
confidence: 99%
“…Thus, the assay used to identify HvnA and HvnB did not distinguish between ARTase or NADase activity. Secreted bacterial ARTases clearly mediate defined effects on certain animal host cells (15,(39)(40)(41), but the role, if any, of secreted NADases in bacterium-host interactions is unknown beyond the observations that clinical streptococcal isolates and Vibrio cholerae secrete NADases (24,52).…”
mentioning
confidence: 99%
“…VPI-2 also encodes sialic acid transport (ORFs VC1777 to VC1779) and catabolism homologues (ORF VC1776 and VC1781 to VC1783), as well as neuraminidase (ORF VC1784), which converts higher-order sialogangliosides to GM1 gangliosides, the receptor for cholera toxin, with the release of sialic acid (6). V. cholerae neuraminidase may also form part of the mucinase complex that hydrolyzes intestinal mucus, enabling the bacterium to move readily to the epithelium (32). Interestingly, none of the four additional published Vibrio species genomes encodes neuraminidase, but they do contain the genes for de novo synthesis of sialic acid, which are absent from V. cholerae (31).…”
mentioning
confidence: 99%